Indonesia’s Support Dynamics Toward Israel: Between Solidarity and National Interests - Mudzakir, Jusril Indra (International Journal of Social Science and Religion (IJSSR), 2025)
This paper explores the dynamics of the Indonesian government and society's support for Israel. By highlighting the attitudes of leaders, religious groups, movements, and various expressions in the media. By using qualitative methods, data obtained through library research and historical and discourse approaches to look deeply at symptoms and phenomena that have occurred and are likely to occur. This research reveals that public attitudes are influenced by religious identity, humanitarian values, and historical narratives disseminated through the media and religious organizations. Solidarity with Palestine has become an integral part of Islamic expression that is deeply rooted in society, driving social movements such as demonstrations, fundraising campaigns, and boycotts of products affiliated with Israel. Religious leaders, Islamic organizations, and social media play an important role in shaping collective perceptions that tend to reject the normalization of relations with Israel. Indonesia's foreign policy towards Israel is based on the principles of anti-colonialism and solidarity with the Palestinian cause. Political, ideological, and societal pressures have shaped this policy, with public opinion largely opposed to normalizing relations with Israel. Nevertheless, economic and trade interactions continue on an informal basis. This research concludes that Indonesian attitudes towards Israel are not only influenced by state policy but also by socio-religious factors that shape transnational solidarity and the collective identity of Muslim communities.